EDUCATION POLICY REFORM IN SOUTH AFRICA: A CASE STUDY ON LEADING CHANGE - Dayaram, Kandy (The journal of contemporary issues in business and government, 2009)
Despite the wide array of studies investigating issues pertaining to leading change, the juggernaut of organisational change continues to be pervasive within the literature. This paper presents empirical evidence of change leadership within the context of education policy reforms in a developing country such as South Africa. The conceptual framework employed to present this evidence and assess the effectiveness of implementing change is the Five-P model. Recent national reforms in South Africa have been accompanied by a re-evaluation of the parity of educational institutions, particularly policies centred on redress and equity of past practices. The results indicate that change leaders are far from transforming their organisations in the ways they intend and that the implementation of change strategies is multifaceted and complex. The paper concludes by emphasising the importance of change leaders developing broader strategies which encompass components of organisational culture and discourse.